Binder Jetting 3D Printing of Titanium Aluminides Based Materials: A Feasibility Study - Yadav, Pinku; Fu, Zongwen; Knorr, Moritz; Travitzky, Nahum (Advanced Engineering Materials, 2020)
This study offers the ability to fabricate nearly dense titanium aluminides-based structures using a hybrid method that encompasses binder jetting 3D printing (3DP) of Ti–6Al–4V followed by pressureless ex situ infiltration with Al. Microstructure characterization and phase analysis are performed by scanning electron microscopy equipped with energy dispersive spectroscopy and X-ray diffraction, respectively. The microstructure of the samples fabricated by means of pressureless ex situ infiltration at different temperatures and with various durations is studied and discussed. The nearly dense titanium aluminides-based composites shows a Young's modulus of ≈145 GPa, a compressive strength of ≈1.4 GPa and a bending strength of ≈483 MPa. To demonstrate technological capability of this hybrid approach, complex near-net-shaped objects are fabricated.
CRIS-Team Scopus Importer:2020-06-09
Keywords: 3D printing; metal-matrix-composites; titanium 6–4; titanium aluminides

Fabrication of Reaction-Bonded Boron Carbide-Based Composites by Binder Jetting 3D Printing - Wahl, Larissa; Schmiedeke, Samuel; Knorr, Moritz; Schneider, Ines; Travitzky, Nahum (Ceramics, 2022)
In this work, the binder jetting 3D printing of boron carbide was combined with a subsequent liquid silicon infiltration procedure to produce reaction-bonded boron carbide (RBBC)-based structures. After printing, the samples were isostatically pressed to obtain more homogeneous and denser microstructures while maintaining their complex shapes. The RBBC bodies were successfully fabricated, and the influence of the binder content on the amount of residual silicon was studied. By increasing the binder content from 10 to 22.5 vol.%, the Si content decreased from similar to 28 to similar to 12 vol.%. The mechanical properties dependent on the Si content were additionally investigated. The measured average values for the bending strength (similar to 355 MPa), Young's modulus (similar to 348 GPa), and hardness (similar to 20 GPa) are comparable to those reported in the literature for RBBC-based materials.
CRIS-Team WoS Importer:2023-01-13